Bienes y servicios ecosistémicos de las plantaciones de Gmelina arborea Roxb (MELINA), en la provincia de los ríos - Maza Cordovillo , Bryan Xavier (2024)
The plantations of Gmelina arborea Roxb. offer a significant variety of goods and ecosystem services that can be managed sustainably to maximize their environmental and economic benefits.. The main objective was to determine the ecosystem goods and services of Gmelina arborea roxb (melina) plantations in the province of Los Ríos. The methodology used in the present study was carried out in fifteen-year-old G. arborea plantations. It was decided to use square plots of 100 x 100 meters (10,000 m²) as sampling units. From each of these plots, subplots of 20 x 25 meters (500 m²) will be taken, placed in the corners of the plots, leaving an adjacent effect space, carried out in the San Carlos y Quevedo parish of the province of Los Ríos. The results reveal that regarding the dasometric variables in G. arborea, the town of Quevedo exhibits the highest average values in Diameter at Breast Height (DBH), with measurements of 30.96 cm and 25.02 cm. The total height averages ranging from 20.77 cm and 20.38 cm were obtained. The commercial volume between the farms obtained averages between 1.08 cm and 0.67 cm. In carbon in the necromass, averages were obtained between 13.63 CN Tm/ha and 12.56 CN Tm/ha. In the cash flow of the financial analysis, an income of $4.221 was obtained for 5 years, maintaining values of USD 10.098.6 12.390.6 and 13.190 during years 8. 12 and 15 respectively. These results provide a quantitative view of the carbon content in different components of the forest ecosystem and also shows the financial analysis of the plantations.